Patterns of care and clinical outcomes in primary oesophageal gastrointestinal stromal tumours (GIST): A retrospective study of the French Sarcoma Group (FSG). Issue 6 (June 2017) - Duffaud, F.; Meeus, P.; Bertucci, F.; Delhorme, J.-B.; Stoeckle, E.; Isambert, N.; Bompas, E.; Gagniere, J.; Bouché, O.; Toulmonde, M.; Salas, S.; Blay, J.-Y.; et al.
Abstract: Background: Oesophageal GIST (ESOGIST) are very rare tumours requiring special consideration regarding diagnosis, surgical management, and perioperative treatment. Methods: A retrospective study was conducted across 9 centres in the French Sarcoma Group (FSG) to characterize all patients in the years 2000–2014. Results: Seventeen patients (pts) with primary localized ESOGIST were identified, with median age 69 years (36–81) and 11 females. Eight tumours (T) occurred in the lower third of the oesophagus, five in the oesophageal gastric junction, two in the superior third, and two in the middle third. All pts underwent oesophagoscopy and/or endoscopic ultrasound (EUS) and CT scan. Fifteen had EUS guided biopsy. Nine pts received Imatinib (IM) as initial treatment resulting in six PR, three SD. Tumours were resected in nine pts (53%) (7 upfront, 2 after IM); via enucleation in four (44%) [median size 4 cm], oesophagectomy in five (56%) [median size 10 cm]. Resections were R0 in three pts (33%), R1 in six (66%). Eight pts (47%) had no tumour resection, and one patient was never treated. Six pts received adjuvant IM. With a median follow-up of 24 months (7–101), 11 pts are alive (64.7%), five died (29.4%), one was lost to follow-up. Two pts of 4 pts relapsed following enucleation. Conclusions: ESOGIST can be reliably identified pre-operatively by EUS-guided biopsy. Surgery for ESOGIST is either enucleation or oesophagectomy depending on tumour size, location, and patient's individual surgical risk. Preoperative IM therapy could improve resectability and should be considered if surgery is contraindicated or would lead to negative impact on the functional status of the patient.